Green financing in Germany: regulatory issues - Ermakova, Elena P. (Journal of the Belarusian State University. Law, 2020)
The article analyzes the German regulatory acts governing the issuance of green bonds as of March 1, 2020. It is proved that the regulatory framework for green financing in Germany is fully consistent with EU law (regulations and directives), which has direct effect in the country. No special national acts in the field of green financing have yet been created in Germany: general laws governing the issuance of corporate securities and environmental laws apply to green bonds. The issue of green bonds in Germany is carried out on the basis of an international non-binding act – the «Green Bonds Principles» of 2018 of the International Capital Market Association. All this leads to uncertainty in the sphere of regulation of green financing, and, as a result, to Germanyʼs lag in the volume of green bond issues.
Keywords: European Union law; German law; green financing; sustainable financing; taxonomy; Paris Agreement; Principles of green bonds